Brain swelling and mannitol therapy in adult cerebral malaria: a randomized trial. - Mohanty, S; Mishra, S; Patnaik, R; Dutt, A; Pradhan, S; Das, B; Patnaik, J; Mohanty, A; Lee, S; Dondorp, A (2011)
BACKGROUND: Coma is a frequent presentation of severe malaria in adults and an important cause of death. The role of cerebral swelling in its pathogenesis, and the possible benefit of intravenous mannitol therapy to treat this, is uncertain. METHODS: A computed tomographic (CT) scan of the cerebrum and lumbar puncture with measurement of cerebrospinal fluid (CSF) pressure were performed on admission for 126 consecutive adult Indian patients with cerebral malaria. Patients with brain swelling on CT scan were randomized to adjunctive treatment with intravenous mannitol (1.5 g/kg followed by 0.5 g/kg every 8 hours; n = 30) or no adjunctive therapy (n = 31). RESULTS: On CT scan 80 (63%) of 126 patients had cerebral swelling, of whom 36 (29%) had moderate or severe swelling. Extent of brain swelling was not related to coma depth or mortality. CSF pressures were elevated (≥200 mm H(2)O) in 43 (36%) of 120 patients and correlated with CT scan findings (P for trend = .001). Mortality with mannitol therapy was 9 (30%) of 30 versus 4 (13%) of 31 without adjunctive therapy (hazard ratio, 2.4 [95% confidence interval, 0.8-7.3]; P = .11). Median coma recovery time was 90 hours (range, 22-380 hours) with mannitol versus 32 hours (range, 5-168 hours) without (P = .02). CONCLUSIONS: Brain swelling on CT scan is a common finding in adult patients with cerebral malaria but is not related to coma depth or survival. Mannitol therapy as adjunctive treatment for brain swelling in adult cerebral malaria prolongs coma duration and may be harmful.